Lexeme oath and its Synonyms in the Lexicographical Sources (Linguostylistic Studies, 2017)
The article deals with the in-depth analysis of the lexemes used to convey the notion of a promise to observe certain obligations, oaths of allegiance to a certain matter. It has been revealed that in modern Ukrainian language the noun lexemes prysiaha, obitsianka, obitnytsia, obit, kliatva, bozhba and rota are used to perform this function. The author remarks that the lexemes prysiaha, obitsianka , kliatva are the commonly used ones, while the lexemes obitnytsia, obit, , bozhba and rota are stylistically limited, although there was no such differentiation between them until the 20th century. The frequency of the use of this or that lexeme is certified by the number of set expressions fixed in the dictionaries. The study considers the usage of the lexeme prysiaha (oath) as a case study to emphasize the importance of the extralinguistic factors from the standpoint of their influence on the state of the accentuation system of the Ukrainian language. The author asserts the importance of the etymological comments of certain compilers of dictionaries and other lexicographic sources, which provide information about the causes and time of the appearance of the set expression in our language, present identical expressions from other Slavic languages, reflect the semantics of the lexemes in a certain historical period.
Keywords: oath; promise; obitnytsia; obit; bozhba; rota; dictionary; lexicographic source